Pelindungan Tarian Tortor Dan Gordang Sambilan Sebagai Ekspresi Budaya Tradisional Di Indonesia - Nur Anisa Simbolon; Kristina Pujasari Sitompul; Sulastri Krisdayanti Sinambela; Reh Bungana Beru Perangin-angin; Parlaungan Gabriel Siahaan (Universitas 17 Agustus 1945 Semarang, 2024)
The role of the local government of North Sumatra province in the development of Tortor Toba dance and gordang sambilan dance as performing arts that are expressions of traditional culture. EBT (traditional cultural expression) is a form of traditional intellectual property. Tortor is a dance, but the meaning more than the movements states that Tortor is a medium of communication, where through the movements displayed there will be interaction between participation in ceremonies, weddings, and also welcome. On the other hand, the lack of attention of the Indonesian government makes the Tortor dance has no copyright protection, therefore the author is interested in conducting further research on legal protection of the Tortor dance, the important role of the local government of North Sumatra province and the solution that can be provided by the government to the problem of claiming tortor and gordang sambilan dances by neighboring countries. This research uses qualitative descriptive research methods, with normative-empirical legal research types. Data collection techniques are interviews, documentation and data sources from the North Sumatra Provincial Culture and Tourism Office and the owner of the Sihoda dance studio. The finding in this study is that legal protection for Tortor's dance has not provided legal certainty specifically for Tortor's own dance, but the law recognizes the existence of regional arts.